Secondary metabolites from the deep-sea derived fungus Aspergillus terreus MCCC M28183 - Huang, Xiaomei; Wang, Yichao; Li, Guangyu; Shao, Zongze; Xia, Jinmei; Qin, Jiang-Jiang; Wang, Weiyi (Frontiers in Microbiology, 2024)
Aspergillus fungi are renowned for producing a diverse range of natural products with promising biological activities. These include lovastatin, itaconic acid, terrin, and geodin, known for their cholesterol-regulating, anti-inflammatory, antitumor, and antibiotic properties. In our current study, we isolated three dimeric nitrophenyl trans-epoxyamides (1-3), along with fifteen known compounds (4-18), from the culture of Aspergillus terreus MCCC M28183, a deep-sea-derived fungus. The structures of compounds 1-3 were elucidated using a combination of NMR, MS, NMR calculation, and ECD calculation. Compound 1 exhibited moderate inhibitory activity against human gastric cancer cells MKN28, while compound 7 showed similar activity against MGC803 cells, with both showing IC 50 values below 10 μM. Furthermore, compound 16 exhibited moderate potency against Vibrio parahaemolyticus ATCC 17802, with a minimum inhibitory concentration (MIC) value of 7.8 μg/mL. This promising research suggests potential avenues for developing new pharmaceuticals, particularly in targeting specific cancer cell lines and combating bacterial infections, leveraging the unique properties of these Aspergillus-derived compounds.